Beyond conventional treatment: A comprehensive systematic review on the advanced oxidation processes for the removal of malathion pesticide from aqueous environments - Gholamzadeh, Mohadeseh; Naghizadeh, Ali; Gholizadeh, Farzaneh; Derakhshani, Elham (Physics and chemistry of the earth. Parts A/B/C, 2025)
This study presents a systematic review of research focused on the removal of malathion from aqueous solutions. Malathion, recognized as a highly toxic pesticide and a strong inhibitor of acetylcholinesterase, is the central subject of this investigation. This review was conducted through comprehensive searches in reputable databases such as Scopus, PubMed, Science Direct, and Web of Science, with data collection extending until May 2024. A variety of parameters were meticulously evaluated, including the type of catalyst and adsorbent, catalyst size, optimal pH, initial malathion concentration, optimal catalyst concentration, optimal contact time, type of irradiation, removal efficiency, adsorbent dosage, maximum adsorption capacity, and optimal temperature. Out of an initial pool of 630 articles, 74 studies met the inclusion and exclusion criteria and were selected for detailed analysis. The results show that malathion removal efficiencies reported in these studies were generally above 70 %, with some studies achieving up to 100 % removal. This systematic review highlights the significant roles that physical, chemical, and biological processes play in the effective removal of malathion from aqueous environments. [Display omitted] •The review was conducted through comprehensive searches in reputable databases such as Scopus, PubMed, Science Direct, and Web of Science, gathering data from 2013 to 2024.•Various parameters were examined, including authorship, publication year, type of adsorbent, optimal pH, initial concentration of the pollutant, optimal contact time, maximum adsorption capacity, adsorption isotherms, and removal percentage were analyzed.